Membangun Karakter melalui Keindahan Bahasa Al-Qur’an - Urwatul Wusqa (Universitas Islam Negeri Imam Bonjol Padang, 2014)
Al Quran is the book of instructions and guidance for human beings on this earth. Allah does not let the man without a revelation because people will not be able to know the nature of existence as a human being on this earth. Quran is a miracle of the Prophet Muhammad that is ma'nawiyah. Quran is guidance and a cure for humans. Quran is a miracle in pronunciation fluency, uslub (the way of deliver) and tarkib (words and sentences order). Arabic is a nation that showed high appreciation in the express poetry, oral or written. Rhythm, verse rhythms of Arabic poetry and has given to the psychological impact of the Arab nation. language of aesthetics and beauty of the Quran containing matchless language. Quran has given the real evidence of change in a generation that lived with ignorance and darkness which then turned into the best generation ever existed on this earth. Therefore, all of those are due to interactions with the Quran.